Management of anoestrus in dairy cattle with placentrex - TAMULI, M K; TAMULI, S M; KALITA, ARUP; SINHA, C K; BORGOHAIN, B N (The Indian Journal of Animal Reproduction, 2023)
Placentrex, a patent of human placental extract was used through intravenous route for induction of oestrus in heifers (n = 30) and cows (n = 40) of Jersey x Indigenous crosses (Jr x) and in heifers (n = 43) and cows,. (n = 6) of Holstein Friesian x Sahiwal crosses (HF x Sh). Heifers in Jr x group exhibited oestrus with an average interval of 14.2 days and resulted in 73.33 per cent pregnancy while cows in Jr x and HF x Sh groups exhibited oestrus with an average interval of 11.7 and 18.5 days respectively and resulted in 87.5 percent and 75.0 percent pregnancy respectively. Placentrex was injected at interval of 24 hrs for three days @ 10 ml. to all the heifers and cows in Jr x group while @ 15 ml. was used to cows in HF x Sh group and found to be beneficial for induction of oestrus in anoestrus condition.